Future Direction and Challenges of Engineering Technology in Malaysia - Badhrulhisham, Abdul Aziz (2013)

(untitled)
At the end of presentation, participants will be able to: understand the Engineering Technology issues in Malaysia, value the benefits of Engineering Technology to the country, appreciate initiatives in Engineering Technology, experience the challenges faced during the whole process, visualize the Future Direction.